:Pengaruh Gaya Kepemimpinan, Motivasi, dan Disiplin Kerja terhadap Kinerja Karyawan (Studi Kasus: Karyawan PT PLN BATAM: (Case Study: Employees of PT PLN BATAM) - Tiara; Zahra Salsabila (Politeknik Negeri Batam, 2025)
In the context of an institution or organization, Human Resources, both as members and leaders, play a crucial role in achieving organizational goals. This study aims to assess the impact of leadership style, motivation, and work discipline on employee performance at PT PLN Batam. The research method employed is quantitative, involving 100 PT PLN Batam employees at the Corporate Office as the population and sample. Data analysis was conducted using SPSS 26. The results of hypothesis testing indicate that leadership style, motivation, and work discipline significantly influence employee performance at PT PLN Batam. These findings are further supported by simultaneous hypothesis testing results. Recommendations from the researcher include the implementation of suitable leadership styles to motivate employees, increasing motivation through financial incentives, and improving discipline through clear policies and sanctions. Further research is suggested to explore additional variables and apply research findings in the workplace. Keywords: Leadership style, motivation, work discipline, employee performance